Determination of Bloods Lipid of Adult Policlinics in Konya Region, Turkey - YAZAR, H.; TIFTIK, A.M. (Asian Journal of Chemistry, 2010)
In this study, the blood lipid levels of adult policlinics in Konya region, Turkey were determined. Several factors such as central obesity, active-passive cigarette smoking, eating habits, life style, body mass indexes, obstruct sleep syndrome (snoring), sex has been considered for present studies. An interesting correlation was also determined as smoking effects.